Juxtaposing and Jostling: The Art of Writing History? - Jo Somerset (European Journal of Life Writing, 2020)
This reflective essay seeks to question, through my creative practice, methods of writing the history of post-1945 events for a young adult reader. Using creative techniques to add depth to the research, I explore the scope of the future project through a palimpsest diagram as well as poetry, word association and vignettes of my lived experiences.  I compare how other creative writers have treated historical narrative in fiction, memoir and drama. Building on schoalrly debate on the role of life writing in historical processes, both source materials and historiography, the essay analyses the scholarship on postmodern representations of the recent past in literature, including personalised life writing and autobiography as well as novels.  Problems jostle for attention: blank spaces of the historical records, unreliable memories, competing definitions of truth, Western class-bound identity and twenty-first century retrospection. My conclusions suggest that novelistic and lyrical techniques and voices may be an effective medium for shining a spotlight on the themes of the late twentieth century.  The resulting work of auto/history will be written and read through a personal lens which that is at the same time a memoir, history and historiography, which juxtaposes a microscopic life against the constellation of world events.